Influence of steady and turbulent wind on motions, mooring tension, and fatigue performance of a steel OO-Star floating offshore wind turbine - Shu, Jiaqing; Gu, Xiaoqing (Frontiers in Energy Research, 2025)
Floating offshore wind turbines (FOWTs) often operate under turbulent wind conditions. However, to enhance computational efficiency, steady wind is sometimes used as an alternative to turbulent wind, potentially resulting in conservative estimates. Assessing FOWT motion and fatigue performance under both steady and turbulent wind conditions is therefore crucial. This study focuses on an enhanced steel semi-submersible FOWT, adapted from the LIFES50+ OO-Star concrete design. The FOWT is modeled using OPENFAST software under various load scenarios, including steady and turbulent winds with irregular waves, for time-domain analysis. The results reveal that the FOWT experiences reduce motion, tension response, blade root loads, and tower-top loads under steady winds combined with irregular waves, compared to turbulent winds with irregular waves. The blade root and tower top loads are lower under steady winds with irregular waves, indicating that steady wind analysis may yield unfavorable outcomes for FOWTs. The findings in this study offer valuable theoretical insights and technical support for the design and evaluation of FOWTs.